Pengaruh Penerapan Prinsip ESG dan Green Invesment terhadap Nilai Perusahaan Perbankan yang Terdaftar di BEI Tahun 2022-2025 - Maulida Asnawati Rohmadina; Bintis Tianatud Diniati; Alfianis Setiyaning Nur Rohma; Intan Adilia Putri; Rizqy Mufida (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of sustainability concepts in the banking sector has encouraged companies to implement Environmental, Social, and Governance (ESG) principles and develop Green Investment initiatives as part of their long-term business strategies. This study aims to examine the effect of ESG implementation and Green Investment on the firm value of banking companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The research employed a quantitative approach using panel data regression analysis. Model selection was conducted through the Chow, Hausman, and Lagrange Multiplier tests, which indicated that the Random Effect Model (REM) was the most appropriate model for the analysis. The results reveal that ESG has a positive and significant effect on firm value, indicating that better implementation of Environmental, Social, and Governance practices enhances a company's value in the perception of investors and the market. Conversely, Green Investment has a negative and significant effect on firm value. This finding suggests that Green Investment is still perceived as a costly activity and has not yet generated direct economic benefits in the short term. Simultaneously, ESG and Green Investment significantly influence firm value, with the model explaining 35.1% of the variation in firm value. The findings imply that banking companies should continuously improve the quality of ESG implementation and optimize the management of Green Investments to create greater firm value and support long-term business sustainability.